2016
DOI: 10.1016/j.jlp.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical characteristics of externally venting flames: Assessment of fire engineering design correlations using medium-scale compartment-façade fire tests

Abstract: In a fully developed under-ventilated compartment fire, flames may spill out of external openings (e.g. windows); Externally Venting Flames (EVF) pose a significant risk of fire spreading to adjacent floors or buildings. The main aim of this work is to comparatively assess a range of fire engineering design correlations used to describe the external dimensions of the EVF envelope. The predictive accuracy of each correlation is evaluated through comparison with experimental data obtained in a medium-scale compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…For the ventilation under dynamic pressure, some previous studies have proved that the abundance of ventilation is able to active the combustion and increase the MLR . The general explanation is that the air flow over the fuel surface steepens the concentration and temperature gradient of fuel vapor.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…For the ventilation under dynamic pressure, some previous studies have proved that the abundance of ventilation is able to active the combustion and increase the MLR . The general explanation is that the air flow over the fuel surface steepens the concentration and temperature gradient of fuel vapor.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…windows) in case the glazing fails. Fire compartment and opening geometry and the prevailing ventilation conditions are the most significant parameters influencing the EVF geometric and thermal characteristics [5,6,13,15,18,19,25]. During the initial stages of the fire, compartment geometry is important since enclosure dimensions are decisive on how close the initial fire is located in relation to other combustible materials, ventilation openings and compartment boundaries.…”
Section: Fundamental Phenomena Affecting Evfmentioning
confidence: 99%
“…In this context, the main aim of this work is to investigate the fundamental thermal phenomena governing EVF development and their impact on façade systems. Motivated by an increasing number of recent reports [4,5,6] suggesting that existing engineering design methodologies cannot describe with sufficient accuracy the thermal characteristics of EVF, this work emphasizes on the assessment of empirical correlations and design methodologies used to describe EVF and their impact on façade systems. Focusing on the thermal characteristics of EVF that affect the fire safety of a façade system, namely the EVF centreline temperature (Tz) and the EVF-induced heat flux to the façade (q"), the predictive accuracy of various design correlations is evaluated by means of comparison with medium-and large-scale fire tests conducted by the authors and found in literature.…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical model on lateral temperature profile of buoyant window spill plume from a compartment fire was reported by using a 0.8‐m cubic fire compartment with window opening varied from 0.20 m (H) × 0.30 m (W) to 0.35 m (H) × 0.35 m (W), and heat release rate (HRR) differed from 128.3 to 244.4 kW . The geometrical characteristics of externally venting flames was discussed by using a 0.60 m (L) × 0.90 m (H) × 0.60 m (W) fire compartment with window opening 0.20 m (H) × 0.50 m (W), and HRR varied from 79 kW to 233 kW . Among the researches on wall temperature distribution emerging from the opening of a fire compartment, the typical correlation between dimensionless temperature Θ and vertical position z was first proposed by Yokoi and recently reexamined by Lee and Delichatsios .…”
Section: Introductionmentioning
confidence: 99%